2017
DOI: 10.3389/fphys.2017.00797
|View full text |Cite
|
Sign up to set email alerts
|

Human Cardiomyocyte Progenitor Cells in Co-culture with Rat Cardiomyocytes Form a Pro-arrhythmic Substrate: Evidence for Two Different Arrhythmogenic Mechanisms

Abstract: Background: Cardiomyocyte progenitor cells (CMPCs) are a promising cell source for regenerative cell therapy to improve cardiac function after myocardial infarction. However, it is unknown whether undifferentiated CMPCs have arrhythmogenic risks. We investigate whether undifferentiated, regionally applied, human fetal CMPCs form a pro-arrhythmic substrate in co-culture with neonatal rat ventricular myocytes (NRVMs).Method: Unipolar extracellular electrograms, derived from micro-electrode arrays (8 × 8 electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Nonetheless, across all species, treating myocytes with hCIC HC decreased upstroke velocity (UV), decreased peak action potential voltage (V peak ), depolarized RMP, and increased [Ca 2+ ] i ,max relative to untreated controls; the effects increased with gap junction conductance from 1 to 10 nS, with minimal further changes due to cell fusion. Consistent with in vitro experimental work ( Smit et al, 2017 ), simulated treatment of rat cardiomyocytes with hCIC HC led to prolonged APD, depolarized RMP, and decreased UV when compared to control untreated rat cardiomyocytes ( Figure 3B ). As anecdotally noted in the same study ( Smit et al, 2017 ), we also predicted V peak to be decreased when treating with hCICs.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Nonetheless, across all species, treating myocytes with hCIC HC decreased upstroke velocity (UV), decreased peak action potential voltage (V peak ), depolarized RMP, and increased [Ca 2+ ] i ,max relative to untreated controls; the effects increased with gap junction conductance from 1 to 10 nS, with minimal further changes due to cell fusion. Consistent with in vitro experimental work ( Smit et al, 2017 ), simulated treatment of rat cardiomyocytes with hCIC HC led to prolonged APD, depolarized RMP, and decreased UV when compared to control untreated rat cardiomyocytes ( Figure 3B ). As anecdotally noted in the same study ( Smit et al, 2017 ), we also predicted V peak to be decreased when treating with hCICs.…”
Section: Resultssupporting
confidence: 89%
“…Paracrine effects of hCICs on cardiomyocyte electrophysiology and calcium cycling were assumed to be negligible based on findings from Smit et al (2017) and others ( Gray et al, 2015 ; Agarwal et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reviewed by Petsche Connel 22 , other groups have also reported that AF cells could be guided toward cardiac differentiation: rat or human c-kit + -selected cells may acquire a CM phenotype when co-cultured with rat neonatal CMs, and functional communications develop among the cells of the co-culture 14 , 17 . However, this differentiation process occurs with a very low yield and presents limits deriving from a xenogenic co-culture sysytem 36 . Other evidence suggests that the modulation of WNT 15 signaling or exposure to 5-Aza 14 , 15 may induce a CM phenotype in unselected AF cells, but these protocols were also characterized by low differentiation efficiency, and organized sarcomeric structures and spontaneous contraction were not detected.…”
Section: Discussionmentioning
confidence: 99%